2020
DOI: 10.22271/chemi.2020.v8.i3g.9271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biochar on the growth and yield of cotton and maize: A review

Abstract: Improper management of soil along with exhaustive monocropping practices have led to loss of soil structure, salinity and erosion and thereby decreasing the soil productivity. Furthermore, misappropriate application of synthetic fertilizers have driven contamination of food and water, pollution of environment creating an endangerment to human health. Therefore, an urgent need to find an alternative solution in improving the soil health without reduction in the productivity from a unit area in a sustainable man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…These ndings are of paramount importance to the textile industry, as cotton ber characteristics, such as staple length and uniformity, directly in uence the quality and durability of textile products. These ndings unequivocally con rm the positive in uence of biochar and FYM on staple length, with the combined treatment demonstrating the most substantial improvement (Karthik et al 2020;Velmourougane et al 2022).…”
Section: Discussionsupporting
confidence: 54%
“…These ndings are of paramount importance to the textile industry, as cotton ber characteristics, such as staple length and uniformity, directly in uence the quality and durability of textile products. These ndings unequivocally con rm the positive in uence of biochar and FYM on staple length, with the combined treatment demonstrating the most substantial improvement (Karthik et al 2020;Velmourougane et al 2022).…”
Section: Discussionsupporting
confidence: 54%
“…The biochar amendments did not improve cocksfoot productivity and only slightly affected tall fescue productivity in contaminated soil. Studies have reported that in conventional crop production on non-contaminated soil, biochar is recognized as a soil amendment that significantly improves plant productivity 28 . For some crops, e.g., maize, this effect is more pronounced in the second and third years after biochar application.…”
Section: Discussionmentioning
confidence: 99%
“…Tovihoudji et al 2022 found that biochar had a pH of 10.21, with concentrations of 50.03% C, 0.31% total N, and 13.76% ash. So, Biochar increased the availability of nutrients in soil under acidic soil stress condition than other soil type (Uzma et al, 2015 andKarthik et al, 2020). The study showed that the different Biochar based treatment types and doses improved cotton growth and yield.…”
Section: Discussionmentioning
confidence: 97%
“…The addition of Biochar improved availability of nutrient elements, concentrations of basic cations, increased availability of soil water and consequently reducing the impact of osmotic stress. Under acid soils the effect of Biochar enhances soil microbial diversity with increasing cations exchange capacity and crop water availability (Karthik et al, 2020). Elangovan, found that the cotton plant height (Ph) was increased during cotton growing stages under Biochar treatment.…”
Section: Discussionmentioning
confidence: 99%